The devil effect triggered by sexual crimes - Pfundmair, Michaela; Matanovic, Romana (Frontiers in Psychology, 2025)
Previous research has identified a number of stereotypical beliefs about sexual crimes, particularly in relation to child sexual abuse and rape. We suggested that these beliefs may be the result of a negative halo effect (i.e., a single negative attribute biases subsequent impression formation judgments). We therefore hypothesized that mere keyword pairs containing ‘sex’ activate negative schemas that influence judgments of criminal cases. We conducted three studies to investigate this hypothesis. In a focus group interview, we attempted to gain a basic understanding of the hypothesized effect. Two online surveys were used to quantify the initial findings. The results showed that the keywords ‘sex and children’ triggered strong negative schemas such as acts of violence, pedophile offenders, and a desire for harsh punishments. The keywords ‘sex and violence’ activated impressions of a broader range of offenses, but still strongly negative associations about the possible offender and harsh penalties. In contrast, the combined keywords ‘children and violence,’ which served as a control, elicited more heterogeneous responses. Overall, the current findings confirm the idea of a devil effect triggered by sexual crimes. This effect could have serious consequences, from reduced awareness of actual crimes to biased judgments by judges and juries.